Pengaruh Green Economy dan Sustainable Ecotourism terhadap Peningkatan Ekonomi Masyarakat Studi: Ekowisata Mangrove Lembung - Rhentah Melviea Finanda Azis; Darul Islam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Green economy and sustainable ecotourism are currently the main focus in efforts to advance the tourism sector which is not only economically profitable but also environmentally sustainable. The aim of this research is to determine the influence of green economy and sustainable ecotourism on improving the community's economy in the Lembung Mangrove Ecotourism. This research involved 94 respondents consisting of local communities, business actors, tourists and tourism managers in the Lembung Mangrove Ecotourism area. The method used is quantitative using the regression method to test the relationship between the variables green economy, sustainable ecotourism and economic improvement. The results of the analysis show that the two dependent variables contribute significantly to economic growth. Green economy shows a significant positive influence, indicating that the application of green economy principles such as efficient management of natural resources and environmentally friendly technology has a big impact on sustainable economic growth. Meanwhile, sustainable ecotourism also has a significant positive influence through the principles of environmental conservation and empowerment of local communities which supports increased economic prosperity. The results of this hypothesis test confirm that sustainability in the economy and ecotourism is able to create a balance between economic growth and environmental preservation. This research makes an important contribution to the development of sustainable economic policies that support the future of the ecotourism sector.